Examining Systematic Crime Reporting Bias Across Three Immigrant Generations: Prevalence, Trends, and Divergence in Self-Reported and Official Reported Arrests - Bersani, Bianca (Journal of quantitative criminology, 2017)
Objective: Mounting evidence reveals that foreign-born, first generation immigrants have significantly lower levels of criminal involvement compared to their US-born, second and third-plus generation peers. This study investigates whether this finding is influenced by differential crime reporting practices by testing for systematic crime reporting bias across first, second, and third-plus generation immigrants. Methods: This study draws on data from the Pathways to Desistance Study, a longitudinal investigation of the transition from adolescence to young adulthood among a sample of serious adolescent offenders. Self-reported and official reports of arrest are compared longitudinally across ten waves of data spanning 7 years from adolescence into young adulthood for nearly 1300 adjudicated males and females. Results: This study reveals a high degree of correspondence between self-reports of arrest and official reports of arrest when compared within groups distinguished by immigrant generation. Longitudinal patterns of divergence, disaggregated by under-reporting and over-reporting, in self- and official-reports of arrest indicated a very high degree of similarity regardless of immigrant generation. We found no evidence of systematic crime reporting bias among foreign-born, first generation immigrants compared to their US-born peers. Conclusions: First generation immigrants are characterized by lower levels of offending that are not attributable to a differential tendency to under-report their involvement in crime.